2016
DOI: 10.1007/s11043-016-9318-8
|View full text |Cite
|
Sign up to set email alerts
|

A study on photothermal waves in an unbounded semiconductor medium with cylindrical cavity

Abstract: The theory of coupled plasma, thermal, and elastic waves was used to investigate the wave propagation on semiconductor material with cylindrical cavity during photothermoelastic process. An unbounded material, elastic semiconductor containing a cylindrical cavity with isotropic and homogeneous thermal and elastic properties has been considered. The inner surface of cavity is constrained, and the carrier density is photogenerated by an exponentially decaying pulse boundary heat flux. The eigenvalue approach, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Povstenko investigated thermal stresses in an infinite body with a circular cylindrical hole with the Caputo time‐fractional derivative. Some more research on thermoelastic body with cylindrical cavity under different theories can be found in [].…”
Section: Introductionmentioning
confidence: 99%
“…Povstenko investigated thermal stresses in an infinite body with a circular cylindrical hole with the Caputo time‐fractional derivative. Some more research on thermoelastic body with cylindrical cavity under different theories can be found in [].…”
Section: Introductionmentioning
confidence: 99%
“…The silicone (Si) and germanium (Ge) materials are chosen as a semiconductor example to make the numerical simulation (using Maple program). To obtain the main results of the basic quantity fields numerically, the physical constants of semiconducting Si medium and Ge are chosen and given as follows [43][44][45][46]: But, the physical constants of Ge material are given below [20,21]: α 0 = 0.779 × 10 −9 N, τ 0 = 0.00005s, ν 0 = 0.0005s.…”
Section: Discussion and Numerical Resultsmentioning
confidence: 99%
“…For numerical evaluations we chose silicon (Si) as semiconductor elastic crystal material. The constants (parameters in SI unit) of the problem as silicon are listed in Table 1 20,34 :…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…1419 used the thermal memory to discuss the overlap between the Photothermal and the generalized thermoelasticty theories in semiconductor materials with different external fields. Hobiny and Abbas 20,21 studied the non-homogenous semiconductor materials with cylindrical cavity by Photothermal theory. Abo-Dahab and Lotfy 22 used the two-temperature theory to explain the photo-excitation of a semiconductor medium.…”
Section: Introductionmentioning
confidence: 99%